2021
DOI: 10.3390/pathogens10050593
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Glycerophosphocholines in the Cutaneous Lesion Caused by Leishmania major in Experimental Murine Models

Abstract: Cutaneous leishmaniasis (CL) is the most common disease form caused by a Leishmania parasite infection and considered a neglected tropical disease (NTD), affecting 700,000 to 1.2 million new cases per year in the world. Leishmania major is one of several different species of the Leishmania genus that can cause CL. Current CL treatments are limited by adverse effects and rising resistance. Studying disease metabolism at the site of infection can provide knowledge of new targets for host-targeted drug developmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Our analysis also showed that lipids and lipid-like molecules are the most commonly perturbed metabolites and metabolic families in response to infection. These observations concur with a recent study on the serum of hamsters infected with L. donovani [16] and on cutaneous lesions caused by Leishmania major in mice [53]. Previous studies indicated reduction of cholesterol and increased triglycerides in the serum of infected individuals [54][55][56], which may be caused by retention of cholesterol into the parasitophorous vacuole in macrophages [57].…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis also showed that lipids and lipid-like molecules are the most commonly perturbed metabolites and metabolic families in response to infection. These observations concur with a recent study on the serum of hamsters infected with L. donovani [16] and on cutaneous lesions caused by Leishmania major in mice [53]. Previous studies indicated reduction of cholesterol and increased triglycerides in the serum of infected individuals [54][55][56], which may be caused by retention of cholesterol into the parasitophorous vacuole in macrophages [57].…”
Section: Discussionsupporting
confidence: 91%
“… 1 It is well known that Leishmania can alter the metabolic profiles of infected cells including L-arginine metabolism and glycerophosphocholines. 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 These changes can modulate immunological functions in the host to promote parasitic survival. 41 , 43 , 50 , 51 However, the impact of this metabolic reprogramming on the lack of pain experienced by CL patients at the lesion site is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania promastigotes (L. major: strain LV39; L. donovani, strain 1S/Cl2D) were maintained as previously described in (31,32) at 28°C in M199 media supplemented with glutamine, adenosine, folic acid, hemin, HEPES, 10% Fetal Bovine Serum (Sigma-Aldrich, cat. no.…”
Section: Promastigote Assay (Ucsf)mentioning
confidence: 99%
“…Next, we examined alternate substitution patterns on the R 1 aryl ring (Table 5). Movement of the methoxy group from parato the ortho- (29) or meta-positions (30) ablated activity, as did nitrogenation of the ring in the presence (31) or absence (32)(33) of the para-methoxy group. Additional unsuccessful modifications explored included homologation of the paramethoxyphenyl moiety to a para-methoxybenzyl (34), and additional furyl (35) and non-aromatic substituents (36-41); although several of these modifications led to significant improvements in key properties such as reduced host cell toxicity, and improved solubility, permeability, HSA binding, and PFI, none were able to achieve inhibition of parasite replication below 10 µM EC 50 values.…”
Section: Medicinal Chemistry Of Pyrazolopyrrolidinones Establishing P...mentioning
confidence: 99%